ПРУЖНИЙ ЕЛЕМЕНТ ПЕРЕТВОРЮВАЧА ЗУСИЛЬ В СТЯЖНИХ ПРИЗМАХ ОСЕРДЯ СТАТОРА ПОТУЖНОГО ТУРБОГЕНЕРАТОРА - Левицький, А.С.; Зайцев, Є.О.; Смирнова, А.М. (Інститут електродинаміки Національної академії наук України, 2018)
Investigated cylindrical elastic sensor element (ESE) of the force primary converter for the powerful turbogenerators stator tightening prisms core. The method of calculation of tubular ESE is proposed, which allows the design effort design gauges from load changes over a wide range. Analytical relations for calculating the dimensions of the ESE element are determined. Conversion function "force - relative longitudinal strain" with the changing cross sectional area of the element in accordance with Poisson's ratio is obtained.  The relative error caused by the nonlinearity of the conversion function is calculated. The analytical dependencies of the information signal on the force in the elastic element for strain-resistive, capacitive and fiber-optic meters are established. References 12,  figures 7.